Ação da angiotensina II na regulação da dominância folicular em bovinos - Ferreira, Rogério (2010)
The objectives of the present study was to determine the concentration of angiotensin II (AngII) in follicular fluid, to characterize the expression of renin-angiotensin system (RAS) genes in follicular cells and to verify the role of AngII in the follicular wave, using an in vivo model with intrafollicular injection and in vitro model with granulosa cells culture. AngII concentration in follicular fluid increased on dominant follicle during and after deviation. Saralasin inhibited follicular growth in all treated cows (4/4), suggesting that AngII is essential for follicular growth in 7-8mm follicles. However, intrafollicular injection of AngII affected neither follicular growth nor the pattern of follicular dynamics, which were similar to control cows. These results imply that bovine ovarian follicles contain sufficient AngII for follicle development. In another experiment, saralasin inhibitory effect was overcome by systemic FSH supplementation, suggesting that AngII is essential to follicular growth during FSH-low dependence stages. The injection of AngII or angiotensin receptor type 2 (AGTR2) agonist in second largest follicle prevented the expected atresia of subordinate follicle and the treated follicle grew at the same rate as the dominant during 24h. To understand why a single intrafollicular injection of AngII antagonist induces follicular atresia, dominant follicle was injected with saralasin or saline and the cows were ovariectomized 24h later. The inhibition of AngII action decreased estradiol concentration in follicular fluid and abundance of mRNA encoding aromatase (CYP19), 3!-hydroxysteroid dehydrogenase (3!HSD), LH receptor, SerpinE2 and cyclinD2 in granulosa cells. On granulosa cell culture, AngII increased CYP19 expression just in the presence of FSH. Taken together, these results show that AngII is essential for follicular growth, and plays important role in regulating genes involved in granulosa cell proliferation (cyclinD2) and differentiation (LHr, aromatase, 3!HSD), which are necessary for development of the dominant follicle. In conclusion, these data suggest that AngII signaling is involved in follicle growth and dominance in cattle.